Renal resistive index as an early predictor and discriminator of acute kidney injury in critically ill patients; A prospective observational cohort study. - Jelle L G Haitsma Mulier; Sander Rozemeijer; Jantine G Röttgering; Angelique M E Spoelstra-de Man; Paul W G Elbers; Pieter Roel Tuinman; Monique C de Waard; Heleen M Oudemans-van Straaten (PLoS ONE)
Background Acute kidney injury (AKI) complicates shock. Diagnosis is based on rising creatinine, a late phenomenon. Intrarenal vasoconstriction occurs earlier. Measuring flow resistance in the renal circulation, Renal Resistive Index (RRI), could become part of vital organ function assessment using Doppler ultrasound. Our aim was to determine whether RRI on ICU admission is an early predictor and discriminator of AKI developed within the first week. Methods In this prospective cohort of mixed ICU patients with and without shock, RRI was measured <24-h of admission. Besides routine variables, sublingual microcirculation and bioelectrical impedance were measured. AKI was defined by the Kidney Disease Improving Global Outcomes criteria. Uni- and multivariate regression and Receiver Operating Characteristics curve analyses were performed. Results Ninety-nine patients were included, median age 67 years (IQR 59-75), APACHE III score 67 (IQR 53-89). Forty-nine patients (49%) developed AKI within the first week. AKI patients had a higher RRI on admission than those without: 0.71 (0.69-0.73) vs. 0.65 (0.63-0.68), p = 0.001. The difference was significant for AKI stage 2: RRI = 0.72 (0.65-0.80) and 3: RRI = 0.74 (0.67-0.81), but not for AKI stage 1: RRI = 0.67 (0.61-0.74). On univariate analysis, RRI significantly predicted AKI 2-3: OR 1.012 (1.006-1.019); Area Under the Curve (AUC) of RRI for AKI 2-3 was 0.72 (0.61-0.83), optimal cut-off 0.74, sensitivity 53% and specificity 87%. On multivariate analysis, RRI remained significant, independent of APACHE III and fluid balance; adjusted OR: 1.008 (1.000-1.016). Conclusions High RRI on ICU admission was a significant predictor for development of AKI stage 2-3 during the first week. High RRI can be used as an early warning signal RRI, because of its high specificity. A combined score including RRI, APACHE III and fluid balance improved AKI prediction, suggesting that vasoconstriction or poor vascular compliance, severity of disease and positive fluid balance independently contribute to AKI development. Trial registration ClinicalTrials.gov NCT02558166.